A study on the relationship between emotional intelligence and life satisfaction at Niaga Global PLT, Selangor / Mohd Firdaus Che Ibrahim - Che Ibrahim, Mohd Firdaus (Faculty of Business and Management, 2019)
The researcher conducted the study is to identify the relationship between emotional intelligence and life satisfaction. Emotional intelligence is the independent variables and life satisfaction as dependent variables in this finding. There are significant correlation between both variables. Social support, self-esteem and perceived stress are components of emotional intelligence that have either positive or negative influence toward the life satisfaction at particular organization. The researcher conducted the study at Niaga Global PLT, Selangor. Questionnaires are distributed within the organization in order to collect the data for this finding. The researcher interpret the data received using Statistical in Sciences Social Software (SPSS). The objective of this study is to identify the component of emotional intelligence, identify which component of emotional intelligence influence the life satisfaction and the relationship between both variables. The study conducted to observe about connection of both variable among the staff at Niaga Global PLT. The result obtained was documented in depth through this report. The researcher also come up with several recommendations and suggestions for future study.